201k views
4 votes
Solve for 4x2 + x - 6 = 0

1 Answer

2 votes

Answer:
x= (-1+√(97) )/(8) , (-1-√(97) )/(8)

Explanation:

Use the Quadratic Formula .. if you use Completing the Square it'll take longer!!

In general, given
ax^(2) +bx+c=0 , there exists two solutions where:


x=\frac{-b+\sqrt{b^(2) -4ac} }{2a} ,
\frac{-b-\sqrt{b^(2) }-4ac}{2a}

In this case, a=4 , b=1 and c= -6


x= (-1+√(1-4*4*-6) )/(2*4) ,
(-1-√(1-4*4*-6) )/(2*4)

Simplify.


x=(-1+√(97) )/(8) ,
(-1-√(97) )/(8)

User Anthony Mutisya
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.